Who nominates? : a history of the U.S. presidential nomination process / Norman R. Williams. - Williams, Norman R. (Cambridge University Press, 2025)
Who Nominates? is an accessible and non-partisan examination of the presidential nomination process, untangling the byzantine web of legal rules that govern modern nomination procedures in both major political parties. Beginning with the Constitutional Convention of 1787, noted constitutional law scholar Norman R. Williams traces the evolution of party rules and state laws regarding which individuals are entrusted with the power to choose the parties' presidential nominees. Only in the 1970s were ordinary voters fully included in the process, and even today, the rules governing nominations exclude or devalue a large number of voters. Williams' analysis provides context for modern debates about the role and influence of party elites, such as the Democrats' "superdelegates," and examines how the rules governing the process today contribute to the increasingly divisive ideological polarization of presidential contests.